A modified method of vibration surveillance by using the optimal control at energy performance index. (June 2015) - Kaliński, Krzysztof J.; Galewski, Marek A.
Abstract: A method of vibration surveillance by using the optimal control at energy performance index has been creatively modified. The suggested original modification depends on consideration of direct relationship between the measured acceleration signal and the optimal control command. The paper presents the results of experiments and Hardware-in-the-loop simulations of a new active vibration reduction algorithm based on the energy performance index idea modified in such a way, that it directly utilises the acceleration feedback signal. Promising prospects towards real application of the modified method in case of the high speed milling are predicted as well. Highlights: Control law derived on a basis of the energy performance index. Acceleration feedback utilised for control signal calculation. Active force generation by the piezoceramic plate actuator applied. Hardware-in-the-loop simulations experiment results included. Significant vibration reduction obtained.